2017
DOI: 10.1007/s11060-017-2627-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of adult medulloblastoma patients treated with radiotherapy

Abstract: Medulloblastoma (MB) is rare in adults and treatment guidelines are consequently not well-established. Few modern series have reported long-term follow-up and treatment sequelae. We examined long-term outcomes of adult MB patients at one institution. Records of 29 consecutive patients (18 male, 11 female) aged ≥ 18 years who received radiotherapy (RT) for primary MB from 1990 to 2016 were reviewed. Median age at diagnosis was 28 years (range 18-72 years). Seventeen patients were standard risk and 12 were high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The impact of treatment on neurocognition and HRQoL in adult medulloblastoma patients is understudied. A recent study reported impaired neurocognitive functioning (learning and memory, and executive function) shortly after diagnosis [13], while another study reported that adult medulloblastoma patients had problems with executive dysfunction, weakness, ataxia, depression or anxiety about nine years after radiotherapy [14]. These long-term sequelae may subsequently have a negative impact on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of treatment on neurocognition and HRQoL in adult medulloblastoma patients is understudied. A recent study reported impaired neurocognitive functioning (learning and memory, and executive function) shortly after diagnosis [13], while another study reported that adult medulloblastoma patients had problems with executive dysfunction, weakness, ataxia, depression or anxiety about nine years after radiotherapy [14]. These long-term sequelae may subsequently have a negative impact on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term radiotherapyinduced structural sequelae as leukoencephalopathy and radiation-induced vasculopathy relate to neurocognitive deficits [45,46]. Neurocognitive impairment after cranial irradiation is more severe in children, but also prevalent in adults [14]. The boost radiotherapy volume can be reduced to the tumor bed only in children without losing efficacy in comparison to posterior fossa irradiation, if a dose of 50 Gy is sustained [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical removal of the tumor should be followed by craniospinal irradiation and a boost to the posterior fossa in any patient. Radiotherapy increases local tumor control and leads to a prolonged progression free survival [ 4 , 66 ].…”
Section: Radiotherapymentioning
confidence: 99%
“…Tremendous improvements in therapy using a combination of surgery, craniospinal radiotherapy and chemotherapy with vincristine, cisplatin and cyclophosphamide have yielded an overall survival of 70–80%, however, radio-polychemotherapy increases the risk of significant toxicities including neurocognitive impairment, endocrinopathy and neurologic deficits [6, 7]. In addition, many patients need to receive craniospinal irradiation to protect against developing metastasis, which places patients at the risk for significant long-term neurocognitive side-effects and sequelae that may impair their quality of life [8]. Targeted treatment is hence strongly desired based on the aggressive nature of the tumor and treatment-related side effects [9, 10].…”
Section: Introductionmentioning
confidence: 99%